2022
DOI: 10.3389/fgene.2022.817919
|View full text |Cite
|
Sign up to set email alerts
|

A pyroptosis-related gene signature for prognosis and immune microenvironment of pancreatic cancer

Abstract: Pancreatic cancer is one of the most lethal tumors owing to its unspecific symptoms during the early stage and multiple treatment resistances. Pyroptosis, a newly discovered gasdermin-mediated cell death, facilitates anti- or pro-tumor effects in a variety of cancers, whereas the impact of pyroptosis in pancreatic cancer remains unclear. Therefore, we downloaded RNA expression and clinic data from the TCGA-PAAD cohort and were surprised to find that most pyroptosis-related genes (PRGs) are not only overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The signature was further validated in an independent cohort with discrepant ethnicity. Integrating only four gene features, the AUC of the SVM signature for 1-year DFS (0.900 in the training cohort) was significantly larger than the AUCs of other patient and tumour characteristics, including TNM stage and differentiation, and single gene features, and was also greater than the AUCs of most of the previously developed signatures based on more gene features (0.661–0.750) 19–24 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The signature was further validated in an independent cohort with discrepant ethnicity. Integrating only four gene features, the AUC of the SVM signature for 1-year DFS (0.900 in the training cohort) was significantly larger than the AUCs of other patient and tumour characteristics, including TNM stage and differentiation, and single gene features, and was also greater than the AUCs of most of the previously developed signatures based on more gene features (0.661–0.750) 19–24 .…”
Section: Discussionmentioning
confidence: 81%
“…Cancer classification based on gene markers has enhanced prognosis prediction 13–17 . Unlike previous potentially similar studies 19–24 , the present analysis combined the machine learning and bioinformatics methods, which might have enhanced feature-selection efficiency and performance, to comprehensively integrate early-relapse-associated aberrant DNA events identified using WES of cancer samples from a Chinese cohort for prediction of prognosis in resected stage I–II PDAC. The signature was further validated in an independent cohort with discrepant ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to these studies, our study also carried out methods such as survival analysis, ROC and external cohort validation of PMSRPS, but it still has its advantages. First, after knowing the importance of subtyping based on molecular characteristics of cancer for improving clinical treatment decision-making, we did not directly use PRGs to establish a prognostic signature as many previous studies had done (84)(85)(86)(87)(88), but instead identified three stable pyroptosis molecular subtypes based on PRGs expression levels. By analysis, we found that different PRGclusters had different survival outcomes and immune cell infiltration manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, three conventional published signatures (Wang's signature [66], Tao's signature [67] and Dai's signature [68]) and two classical prognostic signatures (PAMG [69] and PurIST [70] signature) in PC were collected to compare the predictive accuracy of the IRS and these signatures. For three conventional signatures, we calculated the risk scores based on the genes and coefficients provided by the articles (Supplementary Table 9).…”
Section: Screening Construction and Validation Of The Irsmentioning
confidence: 99%